PERAN PEMERINTAH DAERAH DALAM PENGEMBANGAN PARIWISATA KOTA BIMA SEBAGAI DAERAH TRANSIT WISATA ALTERNATIF - Imam Suyitno; Herman Herman; Nur Hawima (Jurnal Tomalebbi, 2023)
Abstract: This study aims to determine (1) the regulation of the city of Bima in the development of tourism in the city of Bima. (2) The role of the city government of Bima in providing tourism facilities and infrastructure for the City of Bima. This research is a qualitative descriptive study. The types and sources of data used in this study are primary data sources and secondary data sources. Data collection techniques were obtained through observation, interviews and documentation. The focus of this research is related to the important role of the Bima City government through planning, regulation and budgeting in an effort to increase the tourism potential of the city of Bima. Thus, it is clear that the aspects that will be examined in this research are roles, regulations, and implementation.The results of the study show that (1) the regulations issued by the Bima City Government in the development of tourism in the City of Bima, namely the Regional Regulation in the City of Bima Number 9 of 2011 concerning Business Service Retribution which was later changed to the Regional Regulation of the City of Bima Number 2 of 2020 concerning Business Service Retribution for the interest of retribution for tourist attractions in the City of Bima, and Regional Regulation Number 6 of 2015 concerning Tourism for the development of tourist sites in the City of Bima. As well as utilizing other Regional Apparatus Organizations in the Bima City area to assist the development of tourism in Bima City such as Agriculture, Fisheries, Settlement and others. (2) The role of the Bima City Government in providing facilities and infrastructure in Bima City is by providing several facilities and infrastructure in two leading tourist destinations in Bima City, namely Lawata Beach and Kolo Beach such as water baths, banana boats, rolling donuts, tourist boats, and swimming pools. , canoes, prayer rooms, toilets and selling stalls to improve the economy of the community around the tourist beach. As well as regulating the tariff for the use of infrastructure facilities for tourists in the Bima City Regional Regulation Number 2 of 2020 concerning the Change of Faith in the Bima City Regional Regulation Number 9 of 2011 concerning Business Service Retribution in supporting the provision and maintenance of facilities and infrastructure.           Keywords: Government Role, Regulation and Implementation, Tourism Development Abstrak, Penelitian ini bertujuan untuk mengetahui (1) regulasi pemerintah Kota bima dalam pengembangan pariwisata di Kota Bima. (2) Peran pemerintah Kota bima dalam menyediakan sarana dan prasarana wisata Kota bima. Penelitian ini merupakan penelitian deskriptif kualitatif. Jenis dan sumber data yang digunakan dalam penelitian ini adalah sumber data primer dan sumber data sekunder. Teknik pengumpulan data diperoleh melalui observasi, wawancara dan dokumentasi. Fokus penelitian ini adalah berkitan dengan peran penting pemerintah Kota Bima melalui perencanaan, regulasi dan anggaran dalam upaya meningkatkan potensi pariwiata Kota Bima. Dngan demikian, jelas bahwa aspek yang Akan diteliti dalam penelitian ini adalah peranan, regulasi, dan penyelenggaraan.            Hasil penelitian menunjukkan bahwa (1) Regulasi yang dikeluarkan Pemerintah Kota Bima dalam pengembangan pariwisata di Kota Bima yakni Peraturan Daerah di Kota Bima Nomor 9 Tahun 2011 tentang Retribusi Jasa Usaha yang kemudian diubah menjadi Peraturan Daerah Kota Bima Nomor 2 Tahun 2020 tentang Retribusi Jasa Usaha untuk kepentingan retribsui tempat wisata di Kota Bima, dan Peraturan Daerah Nomor 6 Tahun 2015 tentang Kepariwisataan untuk pengembangan lokasi tempat wisata di Kota Bima. Serta memanfaatkan Organisasi Perangkat Daerah lainnya di wilayah Kota Bima dalam membantu pengembangan pariwisata di Kota Bima seperti Pertanian, Perikanan, Pemukiman dan lain-lain. (2) Peran Pemerintah Kota Bima dalam menyediakan sarana dan prasarana di Kota Bima yaitu dengan menyediakan beberapa sarana dan prasarana di dua destianasi wisata unggulan Kota Bima yaitu Pantai Lawata dan Pantai Kolo seperti Pemandian air, banana boat, roling donat, kapal wisata, kolam renang, kano, mushollah, toilet serta lapak-lapak jualan untuk peningkatan ekonomi masyarakat di sekitar pantai wisata. Serta mengatur mengenai tarif penggunaan sarana prasaran bagi wisatawan pada Peraturan Daerah Kota Bima Nomor2 Tahun 2020 tentang Perubahan Ketia Atas Peraturan Daerah Kota Bima Nomor 9 Tahun 2011 tentang Retrubusi Jasa Usaha dalam menunjang penyediaa dan perawatan sarana dan prasarana. Kata Kunci: Peran Pemerintah, Regulasi dan Penyelenggaraan, Pengembangan pariwisata